Subtle inflammation: A possible mechanism of future cardiovascular risk in obese children - Watchareewan Sontichai (2018)
© 2017 by The Korean Pediatric Society. Purpose: The risk of cardiovascular disease (CVD) has been shown to be associated with systemic inflammation in obese adults with metabolic syndrome (MetS). The aims of this study were to evaluate the prevalence of MetS and its relation to inflammatory markers in obese Thai children. Methods: A cross-sectional study was conducted. Children with history of endogenous obesity, chronic diseases, drug ingestion, and any acute illness within 2 weeks prior to enrollment were excluded. Their fasting blood glucose (FBG) levels, oral glucose tolerance tests, insulin, lipid profiles, and selected inflammatory markers, including interleukin-6, tumor necrosis factor-alpha, and high-sensitivity C-reactive protein (hs-CRP) levels, were tested. Results: In this study, 58 obese Thai children (female, 20; male, 38) with a mean body mass index z score of 5.1±2.2 were enrolled. The prevalence of MetS and prediabetes was 31% and 17.2%, respectively. None of the children had diabetes. FBG levels, 2-hour glucose levels, and lipid profiles were not statistically different between those with and without MetS. However, obese children with MetS had higher insulin levels and homeostasis model assessment of insulin resistance values. Elevated hs-CRP levels were found in 69% of the cases, although it was not statistically different between the 2 groups. Conclusion: We described a substantial prevalence of MetS in Thai obese children. Regardless of MetS status, two-thirds of the obese children had elevated hs-CRP level, indicating subtle ongoing inflammatory process. This chronic inflammation feasibly predisposes them to CVD in the future, even in children without MetS.